(untitled) (Research, Society and Development, 2021)
The purpose of this study was to evaluate the behavior of dairy calves bred in tropical climate. Six calves of the Girolando breed at 3 months old in average were used. For the elaboration of the ethogram, the focal animal sampling method was used for five days. The Analysis of Variance was run and treatment means were compared by Tukey’s test at 5% probability. Findings show that calves spent more time in the concentrate intake and foraging, the rumination occurred more frequently during the night, and no significant differences were found between the water intake and the leisure activity. The thermoregulation behavior regarding the shadow demand did not differ statistically when compared to the sun rays demand. However, animals remained in the standing position for longer in the afternoon, and spent more time walking in the morning. Statistical differences were found between the playing interaction 1 and the playing interaction 2, and there were no statistical differences between the stereotypy and vocalization. Therefore, the behavioral states were found to be indicators of the good welfare degree for calves kept in a tropical breeding system.